Mantle Cell Lymphoma Case Report - Podzolkov, V.I. (Case Rep Oncol, 2018)
INTRODUCTION: Due to the beginning of the use of immunophenotypic and cytogenetic techniques, new nosological forms of lymphoproliferative diseases have appeared over the past few decades. According to the WHO classification (2008), today there are more than 50 known lymphoproliferative diseases. CASE PRESENTATION: We present the case of a 51-year-old man with lymphoproliferative syndrome. Our patient underwent morphological and immunohistochemical investigations of biopsy materials from the right inguinal lymph node. The morphological picture was characteristic for small cell lymphoma. Immunophenotypically, tumor proliferate cells expressed CD20, CD76b, CD5, and cyclin D, and the tumor immunophenotype matched mantle cell lymphoma. DISCUSSION: At the present stage of the development of medicine, the diagnosis of lymphoproliferative diseases is based on the clinical picture of the disease with the definition of localization and characteristics of the tumor process, morphological study of tumor tissue and cells, and immunophenotypic and/or cytogenetic analyses are mandatory to determine the final diagnosis.